Genetic Analysis for the Diagnosis of Disorders of Sexual Development in Indonesia - Sultana MH Faradz (Journal of Biomedicine and Translational Research, 2016)
Disorders of sex development (DSD) is defined by congenital conditions in which development of chromosomal, gonadal, or anatomical sex is atypical, while in clinical practice this term means any abnormality of the external genitalia. DSD patients have been managed by a multidisciplinary gender team in our center as collaboration between Dr. Kariadi province referral hospital and Faculty of Medicine Diponegoro University. Diagnosis should be established by specific physical examination hormonal, chromosomal and DNA studies; and imaging for most of the cases depending on indication.Since 2004 the involvement of molecular and cytogenetic analysis so far can diagnosed many of the DSD cases. Most of the genetically proven cases were Congenital Adrenal hyperplasia, Androgen Insensitivity syndrome and sex chromosomal DSD that lead abnormal gonadal development.  Many of them remain undiagnosed, further testing such as advanced DNA study should be carried out in collaboration with other center in overseas.The novel genes were found in some cases that contributed for the management of DSD.  Information for medical professionals, patients, family members and community about the availability and necessity of DSD diagnosis should be delivered to improve DSD management and patient quality of life.